2015
DOI: 10.1080/15384101.2014.1000097
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin induces cell cycle arrest and apoptosis by inducing DNA damage and up-regulation of p53 in Leukemia cells

Abstract: Keywords: apoptosis, cordycepin, cytochrome c, Cdc25A, DNA damage, p53, S-phase arrest Abbreviations: ATM, Ataxia telangiectasia mutated; ATR, ATM and Rad3-related; PI, Propidium iodide; PFT-a, Pifithrin-a; XIAP, X-linked inhibitor of apoptosis protein.Cordycepin, an adenosine analog derived from Cordyceps militaris has been shown to exert anti-tumor activity in many ways. However, the mechanisms by which cordycepin contributes to the anti-tumor still obscure. Here our present work showed that cordycepin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 32 publications
3
60
1
1
Order By: Relevance
“…3-HT significantly inhibited the expression of cyclin E1, cyclin A2 and CDK2; thus, preventing the formation of cyclin E-CDK2 and cyclin A2-CDK2 complexes, which play pivotal role in the initiation and progression of the S phase (33), ultimately leading to S phase arrest. The results were in accordance with previous studies that natural compounds induced S phase arrest by inhibiting the expression of cyclin E, cyclin A2 and CDK in different types of human cancer cells (27,28). A previous study reported that h-PNAS-4 induced S phase arrest in ovarian cancer cells via activation of the Cdc25A-Cdk2-cyclin E/cyclin A pathway, the expression of cyclin E and cyclin A were upregulated while Cdc25A was inhibited (34).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3-HT significantly inhibited the expression of cyclin E1, cyclin A2 and CDK2; thus, preventing the formation of cyclin E-CDK2 and cyclin A2-CDK2 complexes, which play pivotal role in the initiation and progression of the S phase (33), ultimately leading to S phase arrest. The results were in accordance with previous studies that natural compounds induced S phase arrest by inhibiting the expression of cyclin E, cyclin A2 and CDK in different types of human cancer cells (27,28). A previous study reported that h-PNAS-4 induced S phase arrest in ovarian cancer cells via activation of the Cdc25A-Cdk2-cyclin E/cyclin A pathway, the expression of cyclin E and cyclin A were upregulated while Cdc25A was inhibited (34).…”
Section: Discussionsupporting
confidence: 93%
“…Some chemotherapy drugs like 5-fluorouracil and 6-mercaptopurine are commonly used to treat lukemias, ovarian and breast cancers, and other types of cancers by damaging cancer cells during the S phase (26). In addition, several other natural compounds, which have exhibited S phase arrest, have also been shown to induce apoptosis (27–29). In the present study, 3-HT reduced the cell viability of ovarian cancer cells partly through arresting cell cycle at S phase, thus, can become a candidate for further research to treat ovarian cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It was later found that cordycepin possesses anti-inflammatory, antioxidative, antithrombotic, and antiadipogenetic activity as well [811]. In LPS-stimulated macrophages, pretreatment with cordycepin suppressed TNF- α expression and stimulated the production of anti-inflammatory cytokines IL-10 and NO [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Cordycepin, also known as 3-deoxyadenosine, is a major active ingredient extracted from Dong-Chong-Xia-Cao and has been suggested to possess anti-leukemia properties323334353637. However, cordycepin quickly loses its activity in animal models due to its short half-life38.…”
mentioning
confidence: 99%